The Multiculturalism of Pesantren: Scaffolding Diversity of Indonesian Society - Bustomi, Abu Amar; Pardianto, Pardianto; Maksum, Imam; rofik, Abdur (AL-WIJDÃN Journal of Islamic Education Studies, 2021)
Indonesia is a unitary state that is formed from diversity and religiosity in all aspects of life, which are united by natural ethics in national bonds. Ethically, this national bond does not justify conflicts for any reason. However, the reality still tends to be vulnerable and has an impact on resistance among religious communities in Indonesia. In the problem of resistance of plurality relations and multiculturalism in diversity and religiosity that has developed in Indonesia, pesantren, an indigenous educational institution, in their journey can be tested to maintain their sustainability with a multi-aspected education model, which constructs the character of santri into a qualified, independent and reformer nationalist personality. Through scientific studies, which are developed in a critical sociological approach of Max Weber, about the existence of multiculturalism in pesantren as a support for the solidarity of diversity and religiosity of society in Indonesia, it was found that pesantren have an existence as micro and macro support for the diversity and religiosity of society in Indonesia. Keywords: Multiculturalism of Pesantren, Scaffolding Diversity, Indonesian Society.